Pemikiran Tasawuf Beudizzaman Said Nursi: Problematika dan Gagasannya: Badiuzzaman Said Nursi's Sufism Thought: Problems and Ideas - Limpad Tuhu Pamungkas (UIN Sunan Kalijaga Yogyakarta, 2023)
Despite its various shortcomings, Sufism is still needed for religious life today in an increasingly secular world. Considering the various attacks launched against Sufism by Islamic puritan and modernist movements, Said Nursi's thoughts can be considered as a middle way to clear up the clouded pre-judgments of Sufism. This study aims to look at the main ideas of Bediuzzaman Said Nursi related to Sufism and the problematic background behind it, as well as to review the challenges faced by Sufism itself.Â To describe Said Nursi's thoughts on Sufism in this paper, the author will describe objectively Said Nursi's writings that speak explicitly about Sufism, then the author also includes interpretive and analytical elements to reach a broader meaning from those texts. The results of the study found that, for Said Nursi, Sufism is very important for the manifestation of the truth of Islam itself, although it cannot be denied that there are also practices in certain Sufism traditions that are not in accordance with the Sunnah. Therefore, by still referring to the legacy of the Sufism tradition, he offered a new Sufistic path (tariqah) which he named haqiqah, which he considered safer and less risky. Yet, the problem is modernism itself has eroded the esoteric dimension of Sufism itself, while puritanism has textually rejected it. Thus, Said Nursi's thought of Sufism which places a strong emphasis on Shari'a should be brought up. Keywords: Said Nursi, Sufism, Haqiqah, tariqah, shariâ€™a, sufism problematics